Evaluation of In Vivo Wound Healing Activity of Bacopa monniera on Different Wound Model in Rats. (29th July 2013) - Murthy, S.; Gautam, M. K.; Goel, Shalini; Purohit, V.; Sharma, H.; Goel, R. K.
Abstract : Wound healing effects of 50% ethanol extract of dried whole plant of Bacopa monniera (BME) was studied on wound models in rats. BME (25 mg/kg) was administered orally, once daily for 10 days (incision and dead space wound models) or for 21 days or more (excision wound model) in rats. BME was studied for its in vitro antimicrobial and in vivo wound breaking strength, WBS (incision model), rate of contraction, period of epithelization, histology of skin (excision model), granulation tissue free radicals (nitric oxide and lipid peroxidation), antioxidants (catalase, superoxide dismutase, and reduced glutathione), acute inflammatory marker (myeloperoxidase), connective tissue markers (hydroxyproline, hexosamine, and hexuronic acid), and deep connective tissue histology (dead space wound). BME showed antimicrobial activity against skin pathogens, enhanced WBS, rate of contraction, skin collagen tissue formation, and early epithelization period with low scar area indicating enhanced healing. Healing effect was further substantiated by decreased free radicals and myeloperoxidase and enhanced antioxidants and connective tissue markers with histological evidence of more collagen formation in skin and deeper connective tissues. BME decreased myeloperoxidase and free radical generated tissue damage, promoting antioxidant status, faster collagen deposition, other connective tissue constituent formation, and antibacterial activity.